National Arogya Fair 2017 Held on 8th-11th September 2017, AU Grounds, Visakhapatnam (International Journal of Ayurveda and Pharma Research, 2017)
Shri Shripad Yesso Naik, Honrable Minister of State (IC), Ministry of Ayush, Government of India addressing the visitors, exhibitors & Govt. officials at Arogya Fair.Caption-L-R: Smt. Sujata Sharma, Commissioner, Department of Health & Family Welfare & Directorate of AYUSH, Govt. Of Andhra Pradesh, Dr. Smt. Poonam Malkondiah, Principal Secretary, Health and Family Welfare, Govt. Of Andhra Pradesh, Smt. Rambilli Lalam Bhavani, Chairperson of Visakhapatnam Zilla Praja Parishad, Sri. Kambhampati Hari Babu, Member of Parliament, Visakhaptanam, Mr. Anil Khaitan, Senior Vice President, PHD Chamber, Prof. Rais Ur Rahman, Advisor, Ministry of AYUSH, Govt. of India, Shri Ramanand Meena, Deputy Secretary, Ministry of AYUSH, Govt. of India. Sri Vishnu Kumar Raju, Member of Legislative Assembly, Visakhapatnam and Mr. Vivek Seigell, Principal Director, PHD Chamber.Mr. Anil Khaitan, Senior Vice President, PHD Chamber addressing the delegates at the Inaugural Session of National Arorogya Fair 2017 at Visakhapatnam.Shri Shripad Yesso Naik, Honable Minister of State (IC), Ministry of Ayush, Government of India, Inaugurating the National Arorogya Fair.